Low cardiopulmonary fitness is associated with higher liver fat content and higher gamma‐glutamyltransferase concentrations in the general population – "The Sedentary's Liver". (28th January 2022) - Zinterl, Ines; Ittermann, Till; Schipf, Sabine; Gross, Stefan; Anspieler, Henryke; Kim, Simon; Ewert, Ralf; Bülow, Robin; Kühn, Jens‐Peter; Lerch, Markus M.; Völzke, Henry; Felix, Stephan Burkhard; et al.
Abstract: Background: We investigated the association between low cardiorespiratory fitness and liver fat content (LFC) in the general population. Materials and Methods: We evaluated data from 2151 adults (51.1% women) from two population‐based cohorts of the Study of Health in Pomerania (SHIP‐2 and SHIP‐TREND‐0). We analysed the cross‐sectional associations of peak oxygen uptake (VO2peak ) with LFC, assessed by magnetic resonance imaging proton density fat fraction, as well as serum gamma‐glutamyltransferase (GGT) and aminotransferase concentrations by multivariable regression models. Results: We observed significant inverse associations of VO2peak with LFC and serum GGT, but not with serum aminotransferase levels. Specifically, a 1 L/min lower VO2peak was associated with a 1.09% (95% confidence interval [CI]: 0.45‐1.73; P = .002) higher LFC and a 0.18 μkatal/L (95% CI: 0.09‐0.26; P < .001) higher GGT levels. The adjusted odds ratio (OR) for the risk of prevalent hepatic steatosis (HS) by a 1 L/min decrease in VO2peak was 1.61 (95% CI: 1.22‐2.13; P = .001). Compared to subjects with high VO2peak, obese and overweight individuals with low VO2peak had 1.78% (95% CI: 0.32‐3.25; P = .017) and 0.94% (95% CI: 0.15‐1.74; P = .021) higher mean LFC, respectively. Compared to those with high VO2peak, low VO2peak was independently associated with a higher risk of prevalent HS in the obese (adjusted‐OR 2.29, 95% CI=1.48‐3.56; P < .001) and overweight (adjusted OR 1.57, 95% CI=1.16‐2.14; P = .04) groups. Conclusions: Lower VO2peak was significantly associated with greater LFC and higher serum GGT levels in a population‐based cohort of adult individuals. Our results suggest that low VO2peak might be a risk factor for HS.